Rail policies in Turkey after 2002: Is there a modal shift?. Issue 3 (September 2022) - Solak, Ali Osman
Since 2002, the Turkish government has increased its interest in rail transport after neglecting it for more than half a century. The government invested significant sums in the high-speed network and allocated substantial funds for the modernization of conventional rail infrastructure, the expansion of the network, and the construction of logistics centers. In addition, in 2013, the government restructured the rail market and opened it to competition. This paper examines recent rail policy in terms of modal shift to determine whether there is a radical shift in national transportation policy, which has been dominated by road programs. Despite significant steps to help rail achieve a breakthrough, our analysis does not show a strong shift in investment priorities that would lead to modal shift.